Factors affecting the employment of Industrial workers within Narathiwat province - Sojipan, Weerasak; Palasai, Wasan; Sakulrat, Benjaree (Princess of Naradhiwas University Journal, 2019)
This research aims to study the factors that affect the employment of the Industrial workers within Narathiwat. Analysis results by complex regression equations Shows the value of import-export goods. Gross products, provinces, electricity consumption, industrial and registered capital have an impact on hiring industrial workers. Narathiwat is also a highly potent area due to the Malaysia’s Kelantan state contact area. There are three permanent border points contributing to the border trade and also the Thai-Malaysian Friendship Bridge, as well as a tourist area of commerce and services by the target industry. Halal products and logistics, which makes Narathiwat the province must employ employment to meet consumers ‘ needs.